Hubungan Keseimbangan Tubuh Dan Kebugaran Fisik Terhadap Kualitas Hidup Pada Lanjut Usia Di Daerah Urban Surakarta - Bahertha Rachmatika; Dwi Rosella Komalasari; Agus Widodo; Farid Rahman (Universitas Malahayati Lampung, 2022)
ABSTRACT The elderly experience a decrease in body function including a decrease in body balance and physical fitness which can affect the quality of life of the elderly. This study examines the relationship between balance and physical fitness on the quality of life of the elderly in urban Surakarta. The number of participants was 94 elderly people aged 60 years using the quota sampling technique. This research uses quantitative methods (analytic observational) with a cross-sectional study approach. Dynamic balance (TUG) and static balance (mCTSIB) affected the quality of life with p-value 0.05. History of falls as the dominant factor affecting quality of life with p-value = 0.041 and OR = 17.394 (95% CI = 0.719 – 34.069). Meanwhile, dynamic balance is the second dominant factor affecting the quality of life of the elderly in urban areas with a p-value of 0.001 and OR of -3.618 (95% CI = -5.655 - 1.580). The third factor that will affect the quality of life of the elderly in urban balance is static with a p-value of 0.031 and an OR of 0.748 (95% CI = 0.071 – 1.425). There is a relationship between balance with the quality of life of the elderly and physical fitness does not affect the quality of life of the elderly. The history of falls is the first dominant factor, the second by dynamic balance, and the third dominant factor is static balance. Keywords: Balance, Physical Fitness, Quality Of Life, Elderly ABSTRAK Lansia mengalami penurunan fungsi tubuh termasuk penurunan keseimbangan tubuh dan kebugaran fisik yang dapat mempengaruhi kualitas hidup lansia. Penelitian ini meneliti hubungan keseimbangan dan kebugaran fisik terhadap kualitas hidup lansia di urban Surakarta. Terdapat 94 lansia usia ≥60 tahun yang diambil secara quota sampling di Desa Gonilan Surakarta. Pada penelitian ini menggunakan teknik cross sectional study. Keseimbangan dinamik (TUG) dan keseimbangan statik (mCTSIB) mempengaruhi kualitas hidup lansia di urban ( p 0.05). Faktor dominan yang mempengaruhi kualitas hidup lansia di rural adalah riwayat jatuh (p= 0.041, OR = 17.394, 95% CI = 0.719 – 34.069), keseimbangan dinamik (p= 0.00, OR -3.618, 95% CI = -5.655 - 1.580). Dan keseimbangan statik dengan (p=0.03, OR 0.748, 95% CI = 0.071 – 1.425). Terdapat hubungan antara keseimbangan dengan kualitas hidup lansia dan kebugaran fisik tidak mempengaruhi kualitas hidup lansia. Riwayat jatuh sebagai faktor dominan pertama, kedua oleh keseimbangan dinamik, dan faktor dominan ketiga keseimbangan statik. Kata Kunci: Keseimbangan, Kebugaran Fisik, Kualitas Hidup, Lanjut Usia